Control of microgrids - Ng, Teng Win (Nanyang Technological University, 2020)
A microgrid is a small and localized group of electrical sources and loads that operates synchronously with the main power grid. Collectively with Distributed Generations (DG) and Energy Storage Systems (ESS), they aid in improving the reliability and stability of microgrid using power condition and control system which consists of the usage of power converters. The increased penetration of Distributed Generation is challenging the entire architecture of traditional structure of electrical power system as most of them are based on renewable energy sources. This project aims to analyze and provide an overview of Distributed Generation and DC loads integrating into the microgrids, their control and modulation techniques based on the simulate of their validity and effectiveness through MATLAB Simulink.